Cui Bono: العرب، كرة القدم والدولة - Ben Porat, Amir (Jama’a: an Interdisciplinary Journal of Middle East Studies, 2015)
Soon after its renewal in 1949, football clubs from the Arab sector began to partake in the Israeli Football League. At first they participated in lower leagues, but as time passed and Arab clubs multiplied, they began to advance upwards – and, in 1997 Hapoel Tayibe was promoted to the National League (top flight). Football has always been present in the Arab community in Israel. The question this article deals with is: what did football contribute to Arabs in Israel? The answers to this question is discussed in three levels: players, local community, and national Arab community in Israel. The player level clearly shows that football granted Arab players prestige and income. Football created mobility paths which by-pass ethnic-national boundaries: Arab players joined Jewish clubs, played for the Israeli national team, and even for European clubs. Regarding the second level, the article shows that football contributed to the modernisation of the local Arab community, to cultural life (mainly for younger people), and to local and sectarian pride – as seen, for instance, when the whole Arab sector took pride in the success of Bnei Sakhnin United Football Club. Where else do Arabs face Jews on equal terms, and often the former prevail over the latter? In third level, football contributed to solidifying the ethnic-national awareness of the Arab community in Israel. Encounters with anti-Arab, Jewish supporters in football stadiums also ‘forced’ a re-thinking among Arabs who wished to flatten their ethnic-national identity-components – as awareness and protest became tools for attaining integration, sans preconditions. There is no longer need for one to self-identify as a Zionist to feel included when the national team enters the football pitch.